A descriptive study of pain treatment and its follow-up in primary care of elderly patients after orthopaedic care - Gabriella Caleres (Journal of Pharmaceutical Health Care and Sciences, 2020)
Abstract Background Pain treatment post orthopaedic care in the elderly is complicated and requires careful follow-up. Current guidelines state all patients prescribed opioids should have a plan for gradual reduction, with the treatment progressively reduced and ended if any pain remains after more than three months. How this works in primary care remains to be explored. The aim was to describe pain treatment and its follow-up in primary care of elderly patients after orthopaedic care. Methods In this descriptive study, medical case histories were collected for patients ≥ 75 years, which were enrolled at two rural primary care units in southern Sweden, and were discharged from orthopaedic care. Pain medication follow-up plans were noted, as well as current pain medication at discharge as well as two, six and twelve weeks later. Results We included a total of 49 community-dwelling patients with medication aid from nurses in municipality care and nursing home residents, ≥ 75 years, discharged from orthopaedic care. The proportion of patients prescribed paracetamol increased from 28/49 (57%) prior to admission, to 38/44 (82%) after 12 weeks. The proportion of patients prescribed opioids increased from 5/49 (10%) to 18/44 (41%). Primary care pain medication follow-up plans were noted for 16/49 patients (33%). Conclusions Many patients still used pain medication 12 weeks after discharge, and follow-up plans were quite uncommon, which may reflect upon lacking follow-up of these patients in primary care.